ANALISIS PREFERENSI KONSUMEN TERHADAP PEMBELIAN BERAS DI KLATEN - Prasetyo, Agung; Priandini, Visa; Mahananto, Mahananto; Supriyadi, Teguh (Jurnal Ilmiah Hijau Cendekia, 2024)
Food is the most basic human need. Trading Business (UD) Sumber Barokah is a trading business engaged in milling activities and supplying various kinds of rice originating from farmers' production in the Klaten area with various qualities to meet consumer needs. This study aims to determine the attributes that consumers most consider in purchasing rice and rice attributes that are consumer preferences at UD—the method of determining the location of the research using the purposive method. And the method of taking samples of respondents is done by accidental sampling method. The data analysis method used is chi-square analysis, Fishbein multi-attribute model, and Likert scale analysis. This study's results indicate that rice's attributes are consumer preferences at UD. Sumber Barokah is rice with moderate prices, fragrant aroma, cleanliness of clean rice, 5 kg packaging, C4 rice type, and incomplete rice integrity (broken grains). Attributes of rice that consumers must consider in purchasing decisions for rice at UD. Sumber Barokah is a price attribute. The order of attributes from the most considered to the least considered is the price of rice, the type of rice, the wholeness of the rice, the packaging of the rice, the cleanliness of the rice, and the aroma of the rice.